Relation Between Iron and Vitamin A Intake with Feritin Levels In Pregnant Women With Trimester III Iron Deficiency Anemia - Ririn Ririn; Yusrawati Yusrawati; Fika Tri Anggraini (Science Midwifery, 2021)
Ferritin is an indicator that is frequently used to measure iron deficiency anemia, especially in the population of pregnant women. Ferritin functions as an iron storage protein that is non-toxic and will be mobilized when needed. Low ferritin levels can lead to iron deficiency anemia. This study aimed to determine the relation between iron and vitamin A intake with ferritin levels in pregnant women with iron deficiency anemia in trimester III. This research is an observational correlative analytic study with a cross sectional approach. The sample in this study was 37 pregnant women with iron deficiency anemia in trimester III with purposive sampling technique. Data on iron and vitamin A intake were taken by using a modified SQ-FFQ (Semi Quantitative Food Frequency Questionnaire) designed by Lipoeto conducted at BMC General Hospital and dr. M.Djamil Padang Hospital from July 2019 to May 2021. The normality test of the data was carried out by Shapiro Wilk test and data were analyzed by using Pearson correlation test. The results showed that the average iron intake was 34.33±3.36 mg/day, vitamin A intake was 888.86±109.95 mcg/day, and ferritin levels were 8.68±2.82 ng/mL. There was a significant relation between iron intake (p= 0.009), vitamin A intake (p= 0.003), and ferritin levels. The conclusion is that there is a relation between iron and vitamin A intake with ferritin levels in pregnant women with iron deficiency anemia in trimester III.